Global Issues - Local Alternatives - Bakhcheva, Iryna; Dalla Costa, Adua; Grill, Anna Katharina; Hua, Yu-Po; Lemos, Davi; Pasha, Syed Saad Ali; Rahman, Mashiyat; Real, Taïs; Zanchetta, Amanda (Universitätsverlag Göttingen, 2021)
After realising their theses' topics were all related to environmental and human sustainability, a group of young researchers from the Erasmus Mundus International Masters in Global Markets, Local Creativities decided they could take action by sharing their research findings in an easily-understandable, non-academic language, impacting communities outside the academic bubble by making knowledge accessible.This book is the result of the ambition of this group of researchers to critically discuss the main issues of our times: environmental emergency and social inequality. Through a collection of thought-provoking case studies, the reader is invited to reflect upon global issues, from the perspective of local initiatives, considering three main aspects of globalisation: space, global dynamics and social scene, and the role of institutions.